Developing nitrogen fertiliser management strategies for wheat (Triticum aestivum) under conservation agriculture practices within the Western Cape - Neethling, Paul Johannes (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.